Secure Pesticide Storage: Facility Size and Location - Thomas W. Dean (EDIS)
This document identifies and answers two basic questions that typically arise when planning to build a secure pesticide storage facility. This document is Fact Sheet PI-29, part of a series from the Pesticide Information Office, Food Science and Human Nutrition Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: April 2004. Revised: November 2004.